Digital Gamification's Effectiveness in Fostering Self-Directed Learning and Competency among Indonesian Cadets - Adhitya Bagus Ainu Wijaya (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
The global maritime sector requires innovative training methods to meet ever evolving STCW competency standards, particularly in soft skills and psychosocial resilience. Digital assisted education, which had been a revelation for furthering self-directed learning result in post pandemic especially in the post pandemic context, had broadened the attention of educators to explore more sophistication such as implementing gamification techniques. This qualitative case study assessed the pedagogical effectiveness of a digital gamification scheme on ten purposefully sampled cadets at Jakarta Maritime University, utilizing Thematic Analysis based on their pre-existing digital exposure and motivational shifts. Results demonstrated very high effectiveness, confirming that high Digital Technology & Gamification Exposure acts as a vital mediator, accelerating adaptation and molding Motivational Dynamics critical for team dynamics. The research also highlights a critical challenge, which is often overlooked in typical self learning situations, that disparities in Perceived Reliability of Device & Connectivity threaten learning equity among students. These findings offer a valuable framework for integrating gamification into the STCW curriculum, providing an additional contribution to maritime education innovation as well as seafarer welfare strategy.